Suicidal ideation among university students during the COVID-19 pandemic: a rapid systematic review with meta-analysis (Research, Society and Development, 2022)
The COVID-19 pandemic brought several behavioral changes in the social, academic and professional spheres, caused numerous deaths and, due to the lack of treatment, imposed social isolation and an adaptation of daily activities, restricted to the remote format, causing emotional and mental instability. in society. Thus, this study aimed to investigate the prevalence of suicidal ideation and associated factors among university students during the COVID-19 pandemic. A Rapid Systematic Review was performed using several databases. Observational studies evaluating suicidal ideation among college students during the COVID-19 pandemic were considered. Articles were assessed for risk of bias by the Joanna Briggs Institute Instrument. Data were extracted for analysis of associated factors and prevalence meta-analysis. Eleven articles were included. The prevalence of suicidal ideation among university students ranged from 1.7 to 19.6%, with a combined prevalence of 12.1% (95% CI: 9.6-15.0%). Factors associated with suicidal ideation were excessive screen time, social isolation, sleep disorders, symptoms of depression, anxiety, post-traumatic stress and being female. The quality of articles ranged from high to low risk of bias. The combined prevalence of suicidal ideation among university students in the period of the COVID-19 pandemic was high, with social isolation and screen time as factors associated with the new context of the pandemic. The findings indicate that support measures should be made available to students during the pandemic to ensure mental health.